Contestation and Polemic of Islamic Thought in Indonesia - Pomalingo, Samsi; Idrus, Nurul Ilmi; Mohammad Basir; Mashadi (Indonesian Journal of Islamic Literature and Muslim Society, 2022)
This study seeks to uncover the intricacies of Islamic thought and the issues that lead to religious polemics in Indonesia. Utilizing a narrative ethnographic approach, this study examines the polemic of religious thought among the “New Islam” groups, namely Jama'ah Tabligh, Wahdah Islamiyah, and former Hizbut Tahrir, as well as “old Islam” (PMII and Ansor) by taking the Gorontalo context. which was carried out in July-September 2021. within the context of Gorontalo. Data were collected from July to September 2021. The findings indicate that the polemics among Muslims primarily revolve around the topic of khilafiyah, such as practices like tahlilan and the issue of wishing Merry Christmas, and extend to ideological matters. This polemic occurs among Muslims affiliated with groups or organizations that possess an epistemological basis of the extreme right (fundamental) in contrast to those with a left (liberal) epistemological basis.